Design and fabrication of zinc oxide multilayers light emitting devices - Tsang, Tony Siu Hou (2013)
Zinc Oxide (ZnO) exhibits a wide band-gap of ~3.4eV and a large exciton binding energy of ~60meV. ZnO has shown a large potential in the development of Ultraviolet (UV) light emitting devices, operating at room temperature. However, the crystal structure of ZnO has hindered its advancement in UV conventional lasers due to the difficulty in facet-cleaving, results in large scattering loss and high laser threshold.